Identification and assessment of cases of malignant hyperthermia triggering under anaesthetic management: analysis of spontaneous reporting database - E. Yu. Kolesnikova; E. O. Zhuravleva; I. L. Asetskaya; K. E. Zatolochina (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
The article provides analysis of the Federal adverse drug reaction database for the period 2009-2014 years, whose goal was to identify and assess cases of malignant hyperthermia after exposure to inhalational anaesthetics. During this time were identified 10 reports satisfying these requirements.